Geochemistry of Formation Water and Its Implications for Petroleum Source Rocks in the Fengcheng Formation, Mahu Depression, Xinjiang, China - Wang, Jian; Zhou, Lu; Liu, Jin; Zhang, Xinji; Luo, Xiaojing; Zhu, Rong; Wu, Yong; Ren, Zhaoyan; Dick, Jeffrey (Frontiers in Earth Science, 2022)
The geochemical characteristics of formation water reflect the sedimentary environment and the sealing conditions of the formation, which are of great significance for oil and gas exploration. We studied formation water in the deep Permian Fengcheng Formation in the Mahu Depression by analysis of chemical composition, stable isotopes, and homogenization temperature and salinity of fluid inclusions. The results show that the formation water has NaHCO3 water type characteristics with high salinity, high HCO3-, low concentrations of Ca2+ and Mg2+ and high pH, and the overall sealing of the formation is well maintained. Na2SO4 type water was found in some places with poor preservation. The fluid geochemistry and alkali mineral distribution in the strata, which are dominated by deep fine-grain mixed deposits, indicate that the main body of the Fengcheng Formation was deposited in an alkali lake sedimentary environment. The isotopic signatures of heavy carbon, negative oxygen isotope drift, light strontium and heavy boron in the strata near the deep fault zone indicate that the Fengcheng formation may have been affected by deep hydrothermal solutions. From the first member to the third member of the Fengcheng Formation, the salinity first increases and then decreases. This low-high-low trend corresponds to the initial stage of alkali lake development followed by strong alkali formation and a final stage of water retreat. The coincidence between the spatial distribution of alkali minerals, high-salinity formation water and source rocks indicates that the alkali lake environment can form high-quality source rocks with good hydrocarbon generation capacity.